Postcolonial camp Hybridity and performative inversions in Zsazsa Zaturnnah. [article]. - Garcia, J. Neil C.
There is a common presumption that queer theory is global and unproblematically so. This paper argues otherwise, by performing a postcolonial reading of Zsazsa Zaturnnah, an extremely popular Philippine "campy" text from 2003, which is easily assimilated into a queer reading that all too devastatingly overlooks its specificities as a postcolonial articulation. In particular, the paper differentiates contemporary Western camp from the postcolonial camp to be found in texts coming from the Global South, whose theories of subjectivity, even if pathetic, remain distinct from postmodernism's understanding of agency, simply because they remain entirely utilizable in anticolonial and nationalist project, as this text itself illustrates. Queer theory's "doctrine" of gender performativity therefore needs to be reinterpreted from the perspective of postcolonia syncretism and/or hybridity, which indeed can be seen to challenge its most basic assumptions regarding the issues of agency and social transformation.